Sostenibilità, diritti, innovazione sociale - Carra, Luca; Milazzo, Natalia; Cima, Sergio; Bianchi, Massimo; Mori, Marco (Unimi Connect - Universo Terza Missione, 2022)
The first volume of the Unimi Connect - Universe Third Mission series features 14 projects covering social inclusion, sustainability and rights. The first section describes activities to support the most fragile: such as the attempt to restore an identity to the victims of the Mediterranean Sea; the outpatient clinic built for the children from the slums of Nairobi; and the project to help the inmates who want to graduate from prison. In the second section, projects dedicated to sustainability find space: such as the University of the Mountain in Edolo or the Milan University's own strategies to reduce the environmental impact of its activities. In the third volume, we find projects focused on human rights: those of people with disabilities, the right to a safe and transparent society, and legal matters concerning international families.